Modelling of ice rubble in the punch shear tests with cohesive 3D discrete element method. Issue 2 (18th January 2019) - Sorsimo, Arto; Heinonen, Jaakko
Abstract : Purpose: This paper aims to simulate a punch shear test of partly consolidated ice ridge keel by using a three-dimensional discrete element method. The authors model the contact forces between discrete ice blocks with Hertz–Mindlin contact model. For freeze bonds between the ice blocks, the authors apply classical linear cohesion model with few modifications. Based on punch shear test simulations, the authors are able to determine the main characteristics of an ice ridge from the material parameters of the ice and freeze bonds. Design/methodology/approach: The authors introduced a discrete model for ice that can be used for modelling of ice ridges. The authors started with short introduction to current status with ice ridge modelling. Then they introduced the model, which comprises Hertz–Mindlin contact model and freeze bond model with linear cohesion and softening. Finally, the authors presented the numerical results obtained using EDEM is commercial Discrete Element Modeling software (EDEM) and analysed the results. Findings: The Hertz–Mindlin model with cohesive freeze bonds and linear softening is a reasonable model for ice rubble. It is trivial that the ice blocks within the ice ridge are not spherical particles, but according to results, the representation of ice blocks as spheres gave promising results. The simulation results provide information on how the properties of freeze bond affect the results of punch shear test. Thus, the simulation results can be used to approximate the freeze bonds properties within an ice ridge when experimental data are available. Research limitations/implications: As the exact properties of ice rubble are unknown, more research is required both in experimental and theoretical fields of ice rubble mechanics. Originality/value: Based on this numerical study, the authors are able to determine the main characteristics of an ice ridge from material parameters of ice and freeze bonds. Furthermore, the authors conclude that the model creates a promising basis for further development in other applications within ice mechanics.